Проза. Драматургия. Публицистика - Горький Максим (Школа классики, 2000)
Экземпляры: аб. (2001) / Инвентарный номер: 43526 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 71 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6